Neuropeptide Substance P Improves Osteoblastic and Angiogenic Differentiation Capacity of Bone Marrow Stem Cells In Vitro. (23rd June 2014) - Fu, Su; Mei, Gang; Wang, Zhao; Zou, Zhen-Lv; Liu, Song; Pei, Guo-Xian; Bi, Long; Jin, Dan
Abstract : Our previous work showed that implanting a sensory nerve or vascular bundle when constructing vascularized and neurotized bone could promote bone osteogenesis in tissue engineering. This phenomenon could be explained by the regulatory function of neuropeptides. Neuropeptide substance P (SP) has been demonstrated to contribute to bone growth by stimulating the proliferation and differentiation of bone marrow stem cells (BMSCs). However, there have been no prior studies on the association between Wnt signaling and the mechanism of SP in the context of BMSC differentiation. Our results have shown that SP could enhance the differentiation of BMSCs by activating gene and protein expression via the Wnt pathway and by translocating β -catenin, which can be inhibited by Wnt signaling blocker treatment or by the NK-1 antagonist. SP could also increase the growth factor level of bone morphogenetic protein-2 (BMP-2). Additionally, SP could enhance the migration ability of BMSCs, and the promotion of vascular endothelial growth factor (VEGF) expression by SP has been studied. In conclusion, SP could induce osteoblastic differentiation via the Wnt pathway and promote the angiogenic ability of BMSCs. These results indicate that a vascularized and neurotized tissue-engineered construct could be feasible for use in bone tissue engineering strategies.